PHPU 2. Mercury, lead, and cadmium content on Aquatic Kangkong (Ipomoea aquatica, Forsk.) from selected areas in the Philippines (2018)
Kangkong (Ipomoea aquatica Forsk.) is a leafy vegetable popular among children and commonly used in Philippine cuisine. It is known to be nutritious but heavy metal contamination is an issue since the plant has the capability to sequester heavy metals found in water effluents from domestic and industrial waste. This study aimed to determine mercury (Hg), lead (Pb) and cadmium (Cd) uptake of kangkong grown in Laguna Lake (Calamba City, Laguna; Tanay, Rizal; and Pasig City, Metro Manila): Angat River in Pulilan, Bulacan; and a swamp in Cavite, the major sources of supply in Metro Manila and suburbs. The heavy metal concentrations at the top, middle and bottom portions of I. aquatica were determined at different locations and periods from Pasig City (2013), Rizal, (2013), Cavite (2013), Laguna (2014-16) and Bulacan (2016). In 2013, the concentrations were highest, on the average, in market samples from Pasig City (16.9ppb Hg and 0.22ppm Cd) and Rizal (6ppm Pb). The heavy metal levels were higher in the plant samples (0.98 - 24.91ppb Hg; 0.11 - 0.66ppm Pb; 0.009 - 0.017ppm Cd) than the water where these were grown (0.1 - 0.54ppb Hg; 0.015 - 0.023pm Pb; 0,002 - 0.003pm Cd) in Laguna and Bulacan. The calculated values to reach the provisional tolerable weekly intake (PTWI) of mercury and provisional tolerable monthly intake (PTMI) of cadmium of samples from Bulacan and Laguna are far beyond the normal eating capacity of a 60-kg person but may pose a high risk to individuals of lesser weight including children.